Wear‐Off of OnabotulinumtoxinA Effect Over the Treatment Interval in Chronic Migraine: A Retrospective Chart Review With Analysis of Headache Diaries. Issue 8 (14th August 2020) - Ruscheweyh, Ruth; Athwal, Bal; Gryglas‐Dworak, Anna; Frattale, Ilaria; Latysheva, Nina; Ornello, Raffaele; Pozo‐Rosich, Patricia; Sacco, Simona; Torres Ferrus, Marta; Stark, Catherine D.
Abstract : Objective: To quantify wear‐off of the response to OnabotulinumtoxinA (OnabotA) treatment over the treatment cycle in chronic migraine at group and individual level. Background: OnabotA administered quarterly is an effective treatment for chronic migraine. However, some patients report that headache recurs before the scheduled follow‐up injection. Methods: In this retrospective chart review performed in 6 university outpatient centers or private practices specialized in headache treatment, 112 patients with a ≥30% response to OnabotA who completed headache diaries over 13 weeks after OnabotA treatment were included (age [mean ± SD] 45 ± 12 years, 82% female, headache days/month at baseline 24 ± 6). Results: Compared to weeks 5 to 8 after injection, headache days/week increased significantly in weeks 12 (+0.52 ± 1.96, 95% CI [0.15, 0.88], P  < .009) and 13 (+1.15 ± 1.95, CI[0.79, 1.52], P  < .001), demonstrating significant wear‐off of the OnabotA effect. Similarly, acute medication days/week significantly increased in weeks 12 (0.38±1.67, CI [0.06, 0.69], P  ≤ .027) and 13 (+0.83 ± 1.76, CI [0.49, 1.16], P  < .001). At an individual level, 57 patients (51%) showed ≥30% wear‐off by weeks 12 and 13, and 28 patients (25%) showed ≥30% wear‐off already by weeks 10 and 11. Age, gender, OnabotA dose or cycle number, or headache center did not predict individual wear‐off. Conclusions: These data show that in clinical practice, on average the response of chronic migraine patients to OnabotA injection shows a clinically significant wear‐off from week 12 after treatment. About 25% of the patients experience wear‐off even by weeks 10 and 11. It must be noted that wear‐off detected in a real‐world study on OnabotA responders can be due to wear‐off of a pharmacological OnabotA effect or a placebo effect, or to regression to the mean effects. This wear‐off phenomenon may negatively affect quality of life of chronic migraine patients under OnabotA treatment. The best way to counteract wear‐off remains to be determined.